Visible body modifications and future employment - Brabant, Whitney; Mizer, Alicia (My University, 2010)
It is important to investigate male and female college students' perceptions on visible body modifications (VBM) in relation to future employment given the uncertain economy and how VBM can be a risk factor in obtaining employment (Kramer, 2006). This nonrandom pilot study examined the perceptions of 79 college students regarding VBM and the effect those modifications have on future employment. It was hypothesized that female college students would report considering VBM to a greater extent regarding future employment. Data was analyzed using: frequencies, crosstabulations, mean comparisons, independent t-tests, along with Cronbach's Alpha reliability analysis. The results indicated one significant gender difference in support of the hypothesis. College career specialists need to focus on male college students who consider the employment consequences of VBM less than females. Implications for future research would include a larger, random, and more diverse sample to be able to generalize to the larger population of college students.
Keywords: Employment interviewing--Psychological aspects; Discrimination in employment; Body art; Body piercing; Tattooing